Bronchoscopic Lung Volume Reduction in Patients with Severe Emphysema - Fernandez-Bussy, Sebastian; Labarca, Gonzalo; Herth, Felix J.F. (Seminars in Respiratory and Critical Care Medicine, 2018)
Bronchoscopic lung volume reduction (BLVR) is a minimally invasive procedure for patients with symptomatic severe emphysema who may not be candidates for surgical lung volume reduction. BLVR has been shown to improve both functional and clinical outcomes with a relatively low risk of severe complications. Any potential candidate to BLVR should be on optimal pharmacological and nonpharmacological treatment. Radiographic and pulmonary function testing provide key data to help identify potential BLVR candidates. A variety of BLVR techniques have been published with different associated benefits and risks. Current strategies include either blocking procedures such as endobronchial valves and intrabronchial valves or nonblocking procedures such as endobronchial coils and bronchoscopic thermal vapor ablation. The aim of this review is to describe current options of BLVR including their efficacy and safety based on available data.
Keywords: emphysema; bronchoscopy; endobronchial valve; bronchoscopic lung volume reduction